Innovative Assessment for the 21st Century Supporting Educational Needs - Shute, Valerie J.; Becker, Betsy Jane. (Springer US : Imprint: Springer, 2010)
Innovative Assessment for the 21st Century Supporting Educational Needs Valerie Shute and Betsy Becker, editors Assessment continues to take center stage in contemporary education, not merely for the data themselves, but for what they can tell us about students and their instructorsand even more important, about educational domains that need upgrading. Success in the technology-driven modern world increasingly depends on new competencies (many of which have yet to be fully identified), requiring new methods for their accurate measurement. Innovative Assessment for the 21st Century asks readers to rethink the way assessment is conducted and competencies are defined, placing the process in the context of lifelong learning across subject domains. This forward-looking dialogue between contributors in education research, practice, and policy examines a range of specific assessment issues, technologies to address these needs, and larger policy concerns. Chapters focus on the most pressing goals and challenges facing the field today, including: " Using assessment to strengthen learning. " Recognizing the natural role of assessment in everyday life. " Creating an assessment culture in the schools. " Improving assessment through evidence-based methods. " Assessing competencies based in new media and technologies. " Making assessment relevant to students and faculty. Innovative Assessment for the 21st Century is a finely detailed blueprint for researchers in education and cognition, as well as for psychometricians in private and government agencies.